PENGARUH SALES GROWTH DAN LEVERAGE TERHADAP MANAJEMEN LABA - Reni Harni; Yessi Anastasia; Nelli Novyarni (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
This study aims to analyze the effect of sales growth and leverage on earnings management is the research objective. Causality test is a research strategy with an archive strategy. The data used in this research is secondary data. The method of analysis is panel data analysis using the eviews application Version 10 and. The population of this study are manufacturing companies listed on the Indonesia Stock Exchange for the period 2017 to 2020. The sample uses a purposive sampling method through criteria. The sample of this research in one period were 20 companies which, if accumulated during the study period, amounted to 80 companies. The results obtained in this study prove that the variable sales growth and leverage partially have a significant effect on earnings management and all sales growth and leverage simultaneously have an effect on earnings management.